Modeling the Rural Banks’ Survival in Semarang City and Regency during the COVID-19 Pandemic - Naufal, Cesario Hanif; Putri, Santi Maudila; Ekaria (Enthusiastic : International Journal of Applied Statistics and Data Science, 2022)
The COVID-19 pandemic has a significant impact on all sectors including the financial sector. Rural banks are one of the financial institutions that has been affected by the pandemic. The pandemic makes debtors unable to repay the loans that can lead to the increase of non-performing loans. This increase will affect the performance of the rural banks which can lead to the liquidation of rural banks. This is reflected by the decrease in the number of rural banks in Indonesia in 2018–2020 periods. On the other hand, it turns out that rural banks in Semarang City and Regency were not affected by the pandemic. Those rural banks are relatively able to survive, which is reflected by the stable level of the bank’s health. Therefore, this study aims to determine factors that affect the survival status of rural banks in Semarang whether they survive or not during the COVID-19 pandemic. To achieve this goal, binary logistic regression was used in this study. The results show that firm size, income growth, and debtors’ quality have a significant effect on the survival status of rural banks in Semarang City and Regency during the COVID-19 pandemic.